METODE PERHITUNGAN MASSA GAS CO2 YANG DISERAP FOTOBIOREAKTOR DENGAN PERSAMAAN GAS IDEAL - Santoso, Arif Dwi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
BPPT conducted the mass of CO2 gas calculation in the gas absorption experimentsÃ‚Â with phytoplankton cultivation in the photobioreaktor (FBR) batch and continous syatemÃ‚Â using the ideal gas equation. This study stated that the method of calculation with theÃ‚Â ideal gas equation is more simple and practical in providing data analysis comparedÃ‚Â with biomass methods. Some things to note in this method include good knowledgeÃ‚Â about the movement of the gas flow diagram of inputs and outputs FBR, an appropriateÃ‚Â gas sampling, and accuracy of measuring instruments. The required data in theÃ‚Â mass calculation of CO2 gas in a batch photobioreactor system was resultant CO2Ã‚Â concentration during measurement. Meanwhile in a continuous systems, the requireddata was CO2 concentration at the reactor input and output , the rate and duration ofÃ‚Â the injection gas.Keywods : massa gas CO2, dry weight, ideal gas formula